Promoting Students' Academic Performances and Interests in Blocklaying and Concreting Works using a Futures-Wheel Instructional Strategy versus Problem Solving: Implications for Sustainable Development - Oviawe, Jane Itohan; Tazhenova, Gulsara S.; Azman, Mohamed Nor Azhari; Abdullah, Arman Shah (Journal of Technical Education and Training, 2021)
The need to identify effective measures to minimize continuous poor academic performance of students in blocklaying and concreting works and other technical subjects/trades led to this study which sought the effectiveness of Future-wheel as compared to the problem solving approach in the instruction in technical colleges.  The study adopted the non-equivalent control group quasi experimental research design. Six research questions and six null hypotheses guided the study. The study was conducted in Edo State, Nigeria. The population for the study consisted of all 604 vocational II blocklaying and concreting works students in the six technical colleges in Edo State as at 2017/2018 academic session. A sample size of 80 vocational II students was drawn using random sampling technique and used for the study. Findings from the study revealed among others that there was significant mean effect of Futures-Wheel instructional strategy on students Mean performance score and interest in blocklaying and concreting works; there was no significant mean effect of gender on students' Mean performance score in Basic Technology. In line with the findings of the study, the educational implication of the findings were highlighted and it was recommended among others that blocklaying and concreting works teachers should be trained in the use of innovative instructional strategies such as Futures-Wheel to facilitate students' academic performance in the subject.